Preparation and application of graphene-loaded bimetallic chalcogenide heterostructure material

The low-temperature sulfuration or selenization of metal salts on oxidized graphene creates dual metal sulfide or selenide heterostructures with rich interface areas, addressing the limitations of existing new energy materials by enhancing their structural stability and performance for oxygen reactions and sodium ion batteries.

CN119680583APending Publication Date: 2025-03-25CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775784.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Current methods for producing new energy materials, such as metal sulfide compounds, face challenges in achieving high performance due to low conversion efficiency, energy density, and cost, particularly in the development of heterogeneous structures that are difficult to scale up for large-scale production.

Method used

A method involving the low-temperature sulfuration or selenization of metal salts on oxidized graphene as a support, using a controlled thermal process to create dual metal sulfide or selenide heterostructures with rich interface areas, allowing for the selection of metal sources to optimize the composition and structure for enhanced catalytic and electrochemical performance.

Benefits of technology

The method results in materials with improved structural stability, electronic conductivity, and catalytic activity, enabling their use as superior catalysts for oxygen reactions and sodium ion battery electrodes with enhanced performance and scalability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680583A_ABST
    Figure CN119680583A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy storage and conversion, and particularly relates to a graphene-loaded bimetallic chalcogenide heterostructure material, preparation and application. The preparation method of the graphene-loaded bimetallic chalcogenide heterostructure material comprises the following steps: 1) dissolving a metal salt in a graphene oxide aqueous solution; and 2) carrying out sulfuration / selenylation calcination (at the temperature of 400-600 DEG C) to obtain a target product. The material prepared by the method disclosed by the invention has a relatively high heterogeneous interface, improves the catalytic activity of oxygen evolution reaction and the sodium storage performance, and is simple in steps, excellent in functional effect and convenient for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a bimetallic chalcogenide material in the field of new energy materials, and in particular to a method for preparing a heterogeneous structure material. Background Art

[0002] Developing the next generation of renewable energy to replace traditional fossil fuels is an important way to build a "clean, low-carbon" social sustainable development. New energy materials, as the key to the development and utilization of new energy, play an important role in optimizing the energy structure. At present, the commonly used lithium-ion battery graphite carbon negative electrode materials cannot meet the needs of new energy vehicles and smart grids due to their relatively low energy density and rate performance; the commercial catalysts of precious metals ruthenium / platinum in fuel cells are expensive, which seriously restricts the development of the new energy industry. Therefore, further expanding the types of new energy materials and selecting appropriate material systems to study the relationship between their structure, composition and performance are of great significance to improving new energy production and realizing their wide application. Among the many new energy materials under research and development, metal chalcogenides (A x B y,A=Fe, Co, Ni, Mo, etc.; B=S, Se, etc.) has the advantages of rich composition elements, high electrochemical activity, easy preparation and environmental friendliness, becoming one of the most promising alternatives to traditional commercial materials. However, there are still many problems such as low conversion efficiency, low energy density and high cost, and it is still in the stage of accumulating power for development. In the past decade, researchers have made great efforts to solve the above problems, which can be summarized into the following two main methods: ⅰ) synthesizing compounds with good size, morphology and structure to optimize the utilization rate of active substances; ⅱ) constructing a stable physical barrier, composite functional carbon materials (conductive polymers, carbon nanotubes and graphene, etc.), improving the conductivity of electrode materials, and buffering the volume change of active materials. However, single metal chalcogenides are limited by their own physicochemical properties and degree of freedom of regulation, and it is difficult to meet people's pursuit of high-performance energy materials. The performance shown in the reaction process still needs to be further improved (Adv. Mater. 2021, 33, 2100855). Recently, a large number of research results have shown the superiority of the construction of heterostructured materials in the field of energy conversion and storage, and have been widely favored by researchers (Angew.Chem.Int.Ed.2021,60,18830-18837.Adv.Mater.2022,34,2104405). Therefore, it is of great significance to develop a process with abundant raw materials, low cost, excellent performance, simple controllability and good repeatability to prepare heterostructured materials. The work reported so far shows that heterostructured materials have excellent electron transport properties, rich active sites, good catalytic activity, etc. However, the traditional construction of heterogeneous interfaces uses epitaxial growth methods, which require precise control of the substrate and epitaxial interface during the preparation process. This process is complicated, has low yield, and is difficult to mass produce. Therefore, how to prepare energy materials with rich heterogeneous interfaces through heterogeneous interface engineering is still a big challenge. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention proposes a method for preparing a bimetallic chalcogenide heterostructure material, the prepared material has a relatively rich heterogeneous interface, and the construction of heterostructure materials with different components can be realized by selecting a suitable metal source. As an oxygen evolution reaction catalyst and a negative electrode material for sodium ion batteries, it exhibits excellent activity and charge-discharge capacity.

[0004] According to the first aspect of the present invention, the present invention provides a bimetallic chalcogenide heterostructure material, in which graphene oxide is used as a supporting carrier, and a sulfur source or a selenium source is reacted with a bimetallic salt by low-temperature sulfurization and / or selenization to form a bimetallic chalcogenide heterostructure material; the bimetallic salt is a metal salt containing Mo and a metal salt containing any one of Co, Ni and Cu; the low temperature refers to 400-600°C.

[0005] Preferably, the double metal salt is a combination of Co and Mo, a combination of Ni and Mo, or a combination of Cu and Mu.

[0006] According to a second aspect of the present invention, the present invention provides a method for preparing a bimetallic chalcogenide heterostructure material, comprising:

[0007] Step 1, dissolving a bimetallic salt in a graphene oxide aqueous solution to complete ion adsorption, and then drying to obtain a precursor; the bimetallic salt is a metal salt containing Mo and a metal salt containing any one of Co, Ni and Cu;

[0008] Step 2, placing the above-mentioned precursor and sulfur source or selenium source in a tube furnace, heating to 400-600° C. at a rate of 2-5° C. / min under an argon atmosphere, and keeping the temperature for 2-4 hours to obtain a final product;

[0009] Preferably, in step 1, one of the bimetallic salts is selected from cobalt nitrate, nickel nitrate, copper nitrate, cobalt chloride, nickel chloride, and copper chloride; the other is selected from ammonium molybdate or sodium molybdate; the sulfur source is selected from sulfur powder or sulfamide; and the selenium source is selected from selenium powder.

[0010] Preferably, the double metal salt contains Co and Mo.

[0011] Preferably, the mass ratio of the bimetal in step 1 is 1:1 / 3 to 3.

[0012] Preferably, the mass ratio of the precursor to the sulfur source (eg, sodium sulfite) and / or the selenium source (eg, selenium powder) is 1:5 to 1:10.

[0013] Preferably, the double metal salt in step 1 contains Co and Mo, and a selenium source is used in step 2.

[0014] Preferably, the pyrolysis time in step 2 is not less than 2 hours.

[0015] Preferably, in step 1, the metal salt is dissolved in the graphene oxide aqueous solution to obtain a black powder; in step 2, the black powder and sulfur powder or selenium powder are placed in a tube furnace, and the temperature is raised to 400-600°C at a rate of 2-5°C / min in an argon atmosphere for 2-4 hours. The experimental results show that the CoSe2 / MoSe2-G sample obtained by calcining the bimetallic chalcogenide heterostructure material at 400°C exhibits excellent activity as an electrocatalyst for oxygen evolution reaction; and the negative electrode material prepared as a sodium ion battery also exhibits excellent performance in rate performance.

[0016] According to the third aspect of the present invention, the present invention provides a use of the above-mentioned bimetallic chalcogenide heterostructure material, which can be used to prepare an oxygen evolution reaction electrocatalyst, or as a negative electrode material for a sodium ion battery; further preferably, the bimetallic chalcogenide heterostructure material is used to prepare an oxygen evolution reaction electrocatalyst.

[0017] Preferably, when used to prepare an oxygen evolution reaction electrocatalyst, the bimetallic materials in the bimetallic chalcogenide heterostructure material are Co and Mo, graphene oxide is used as a support carrier, and the selected precursor and selenium source are placed in a tubular furnace for low-temperature selenization.

[0018] Pre-selected, when used as a negative electrode material for a sodium ion battery, the bimetallic chalcogenide heterostructure material contains Cu and Mo, graphene oxide is used as a supporting carrier, and a precursor and a selenium source are selected and placed in a tubular furnace for low-temperature selenization.

[0019] Graphene is used as a support carrier, metal salts of different components are used as metal sources, and low-temperature sulfurization and / or selenization are used to achieve the formation of bimetallic chalcogenide heterostructure materials. The technical solution provided by the present invention has the following beneficial effects:

[0020] (1) According to different needs, different metal salts can be selected to synthesize heterostructure materials with bimetallic components. The heterogeneous interface can greatly improve the structural stability and electronic conductivity of metal chalcogenides.

[0021] (2) The bimetallic sulfide compounds synthesized by the method of the present invention exhibit excellent electrochemical properties.

[0022] (3) The preparation method of the present invention has simple steps, mild conditions, and is convenient for industrial large-scale production.

[0023] (4) The material prepared by the method of the present invention has a higher heterogeneous interface and improved catalytic activity of oxygen evolution reaction and sodium storage performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM image of the CoSe2 / MoSe2-G20-400 material obtained in Example 1.

[0025] Figure 2 This is the XRD pattern of the CoSe2 / MoSe2-G20-400 material obtained in Example 1.

[0026] Figure 3 This is the HRTEM image of the CoSe2 / MoSe2-G20-400 material obtained in Example 1.

[0027] Figure 4This is the LSV curve of the CoSe2 / MoSe2-G20-400 material obtained in Example 1 at 10 mV / s.

[0028] Figure 5 This is the CP curve of the CoSe2 / MoSe2-G20-400 material obtained in Example 1.

[0029] Figure 6 This is the charge and discharge curve diagram of the CoSe2 / MoSe2-G20-400 material obtained in Example 1. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.

[0031] Example 1

[0032] Take 20mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30 minutes. Then weigh 1.5mmol Co(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30 minutes. Then transfer it to a 50ml reactor and incubate at 150 degrees for 6 hours. Then centrifuge and wash the sample three times, and vacuum dry it at 60℃ overnight to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 between the precursor and selenium powder. In an argon hydrogen atmosphere, heat it to 400℃ at 2℃ / min and keep it for 2 hours. After cooling, collect the black powder for later use. The SEM results show that the morphology of the obtained material is a micro-nano structure on nanorods loaded with graphene (such as Figure 1 ), XRD shows that the material phase is CoSe2 and MoSe2 dual phase (such as Figure 2 ).

[0033] Example 2

[0034] Take 20mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Co(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, then centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat to 600℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for later use.

[0035] Example 3

[0036] Take 40mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Co(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat to 400℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for later use.

[0037] Example 4

[0038] Take 60mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Co(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, then centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat to 400℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for later use.

[0039] Example 5

[0040] Take 60mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Co(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, then centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and sulfur powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: sulfur powder, in an argon hydrogen atmosphere, heat to 400℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for later use.

[0041] Example 6

[0042] Take 20mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Ni(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, then centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat to 400℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for use.

[0043] Example 7

[0044] Take 20mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Ni(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, then centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and sulfur powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: sulfur powder, in an argon hydrogen atmosphere, heat to 400℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for later use.

[0045] Example 8

[0046] Take 60mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Ni(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, at 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat it to 400℃ at 2℃ / min and keep it for 2 hours. After cooling, collect the black powder for use.

[0047] Example 9

[0048] Take 60mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Ni(NO3)2·6H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and sulfur powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: sulfur powder, in an argon hydrogen atmosphere, heat it to 400℃ at 2℃ / min and keep it for 2 hours. After cooling, collect the black powder for use.

[0049] Example 10

[0050] Take 60mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Cu(NO3)2·3H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry to obtain the precursor. Then place the precursor and selenium powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat to 400℃ at 2℃ / min and keep for 2 hours. After cooling, collect the black powder for use.

[0051] Embodiment 11

[0052] Take 60mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 1.5mmol Cu(NO3)2·3H2O and 1.5mmol Na2MoO4·2H2O and put them into the above solution and stir continuously for 30min. Then transfer it to a 50ml reactor, incubate at 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry it to obtain the precursor. Then place the precursor and sulfur powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: sulfur powder, in an argon hydrogen atmosphere, heat it to 400℃ at 2℃ / min and keep it for 2 hours. After cooling, collect the black powder for later use.

[0053] Example 12

[0054] Take 20mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 3mmol Co(NO3)2·6H2O and put it into the above solution and stir it for 30min. Then transfer it to a 50ml reactor, incubate it at 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry it to obtain the precursor. Then place the precursor and sulfur powder at both ends of the quartz boat in a weight ratio of 1:8 for the precursor: selenium powder, in an argon hydrogen atmosphere, heat it to 400℃ at 2℃ / min and keep it for 2 hours. After cooling, collect the black powder for later use.

[0055] Example 13

[0056] Take 20mg of graphene oxide and dissolve it in 25mL of deionized water, and ultrasonically disperse it for 30min. Then weigh 3mmol of Na2MoO4·2H2O and put it into the above solution and stir it for 30min. Then transfer it to a 50ml reactor, 150 degrees for 6 hours, centrifuge and wash the sample three times, and vacuum dry it to get the precursor. Then place the precursor and sulfur powder at both ends of the quartz boat in an argon hydrogen atmosphere, and heat it to 400℃ at 2℃ / min for 2 hours. After cooling, collect the black powder for use.

[0057] The above examples were tested for oxygen evolution catalysis and sodium storage performance, as follows:

[0058] Take 5 mg of the above synthesized sample (active substance) and add 0.5 ml DMF and 0.02 ml naphthol to it, ultrasonically disperse for 60 minutes, take 0.01 ml of the above solution with a pipette and drop it on 1 cm*2 cm carbon paper, dry it in the air, use this as the working electrode, the reference electrode is Hg / HgO, the counter electrode is Pt wire, and the electrolyte is 1M KOH solution. Use CHI760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) at room temperature; mix the synthesized sample (active substance), acetylene black (conductive agent) and PVDF (binder) in NMP at a mass ratio of 7:2:1, then apply it on copper foil and place it in a vacuum drying oven at 100°C for 10 hours. After taking it out, cut it into electrode discs with a diameter of 12 mm. This was used as the negative electrode, metallic sodium as the counter electrode, Whatman glass fiber (GF / D) as the separator, nickel foam as the filler, and the electrolyte was 1M NaClO4 dissolved in propylene carbonate (PC) + fluoroethylene carbonate (FEC) (volume ratio 95:5). CR2032 button cells were assembled in a glove box filled with argon protection. The LAND CT2001A (Wuhan Landian) multi-channel battery test system was used for testing, with a voltage range of 0.01-3.0V and a temperature of room temperature.

[0059] The linear sweep voltammetry obtained from the electrode prepared from the product of Example 1 is as follows: Figure 4 The cyclic stability diagram is shown in Figure 5 As shown, at 10mAcm -2 The constant potential cycling stability under current density, as the charge and discharge curve of the negative electrode material of sodium ion battery, is as follows Figure 6 As shown, at 0.1Ag -1 Under these conditions, the performance was 485 mAhg -1 The oxygen evolution performance and sodium storage performance of the electrodes prepared from the products of Examples 1 to 13 are shown in Table 1 below.

[0060] Table 1 Oxygen evolution performance of electrodes obtained from the products of Examples 1 to 13 and performance of negative electrode materials for sodium ion batteries

[0061]

[0062]

[0063] Note: CoSe2 / MoSe2-G20-400 represents graphene-loaded CoSe2 and MoSe2 dual-phase micro-nanostructure materials. The calcination temperature during the preparation process is 400℃. The definitions of other materials are similar.

[0064] The experimental results show that the bimetallic chalcogenide heterostructure prepared by this method has abundant heterointerfaces.

[0065] As oxygen evolution catalysts, the sulfur / selenide of CoMo and NiMo bimetallic components is superior to the commercial RuO2 noble metal catalyst in terms of overpotential, especially CoMo selenide is the best, while CuMo sulfide and selenide have poor oxygen evolution activity. In addition, from the perspective of the same bimetallic component, the oxygen evolution performance of selenide is better than that of sulfide.

[0066] As the negative electrode material of sodium-ion batteries, in terms of rate performance, the CuMo selenide sample exhibits the highest reversible specific capacity, followed by CoMo selenide, and finally CuMo sulfide. Comprehensive performance comparison results show that CoMo selenide has outstanding performance in both oxygen evolution performance and sodium storage rate performance.

Claims

1. A bimetallic chalcogenide heterostructure material, wherein graphene oxide is used as a supporting carrier, and a sulfur source or a selenium source is reacted with a bimetallic salt by low-temperature sulfidation and / or selenization to form a bimetallic chalcogenide heterostructure material; the bimetallic salt is a metal salt containing Mo and a metal salt containing any one of Co, Ni and Cu; the low temperature refers to 400-600°C.

2. The bimetallic chalcogenide heterostructure material according to claim 1, wherein the bimetallic salt is a combination of Co and Mo, a combination of Ni and Mo, or a combination of Cu and Mu.

3. A method for preparing the bimetallic chalcogenide heterostructure material according to claim 1, comprising the following steps: Step 1, dissolving a bimetallic salt in a graphene oxide aqueous solution to complete ion adsorption, and then drying to obtain a precursor; the bimetallic salt is a metal salt containing Mo and a metal salt containing any one of Co, Ni and Cu; Step 2: Place the above-mentioned precursor and sulfur source or selenium source in a tubular furnace, heat and pyrolyze to 400-600° C. at a rate of 2-5° C. / min in an argon atmosphere, and keep the temperature for 2-4 hours to obtain the final product.

4. The method according to claim 3, wherein one of the bimetallic salts in step 1 is selected from cobalt nitrate, nickel nitrate, copper nitrate, cobalt chloride, nickel chloride, and copper chloride; and the other is selected from ammonium molybdate or sodium molybdate; and / or, the sulfur source is selected from one of sulfur powder and sulfinamide; the selenium source is selected from selenium powder; And / or, the double metal salt contains Co and Mo; And / or, the mass ratio of the bimetal in step 1 is 1:1 / 3 to 3; And / or, the mass ratio of the precursor to the sulfur source and / or selenium source is 1:5 to 1:10; And / or, the bimetallic salt in step 1 contains Co and Mo, and a selenium source is used in step 2; And / or, the pyrolysis time in step 2 is not less than 2 hours.

5. A use of the bimetallic chalcogenide heterostructure material according to claim 1 or the bimetallic chalcogenide heterostructure material prepared by the method according to claim 2 for preparing an oxygen evolution reaction electrocatalyst or as a negative electrode material for a sodium ion battery.

6. The use according to claim 5, for preparing an electrocatalyst for oxygen evolution reaction.

7. The use according to claim 5, when used for preparing an oxygen evolution reaction electrocatalyst, the bimetallic chalcogenide heterostructure material comprises Co and Mo, graphene oxide is used as a supporting carrier, and a precursor and a selenium source are selected and placed in a tubular furnace for low-temperature selenization.

8. The use according to claim 5, when used as a negative electrode material for a sodium ion battery, the bimetallic chalcogenide heterostructure material comprises Cu and Mo, graphene oxide is used as a supporting carrier, and a precursor and a selenium source are selected and placed in a tubular furnace for low-temperature selenization.